Study on serum Lipoprotein (a) level in preeclamptic Bangladeshi women - E-Ferdous, Noor; Khatun, Mahmuda; Siddique, Md Abu; Hosna, Asma Ul; Begum, Shirin Akter; Ahmed, Md Khurshed (University Heart Journal, 2009)
It is a case control study which was design to know the association of serum Lipoprotein (a) level in preeclamptic (PE) in women. This study was carried out in department of Obstetrics and Gynecology, Sir Salimullah Medical College Hospital, Mitford, Dhaka. Total number of subjects was 100. Out of which 50 were cases and 50 were controls. Cases were physically and clinically proved PE patients. Controls were age, parity and gestational age matched. Three ml of blood were collected from each subjects, serum fasting LP(a) level were measured The mean age of study group was 24.49 ± 6.48 years. Serum Lipoprotein(a) level was 51.51 ± 29.38mg/dl Vs 17.40 ± 7.89 mg/dl in cases and controls respectively. This difference was statistically significant (p < 0.001). Mean serum Lipoprotein(a) level was found to be raised in severe preeclampsia (74.87mg/dl) and lowest in control subject Severe preeclampsia was found to be associated with higher level of lipoprotein (a) than both control (p < 0.01) and mild preeclamptic (p < 0.01) subjects. Mild preeclampsia was also found to have higher average serum Lipoprotein (a) than the normal (P < 0.01) subjects. Key Words: Lipoprotein(a), Preeclampsia, Bangladeshi women. doi:10.3329/uhj.v4i2.2073 University Heart Journal Vol. 4 No. 2 July 2008 p32-35